Facts and values: on the acceptability of risks in children's sport using the example of rugby — a narrative review. Issue 15 (19th July 2017) - Quarrie, Kenneth Lincoln; Brooks, John H M; Burger, Nicholas; Hume, Patria A; Jackson, Steve
Abstract : A clash of values has been identified between those who assert that: 1. all childhood injuries, regardless of origin, are inherently undesirable and should be prevented and; 2. those who believe that some measure of injury to children is an acceptable compromise for the physical benefits associated with physical activity and the development of abilities to appraise and deal with risks. A debate regarding whether the tackles and collisions permitted in schools' rugby represent acceptable risks, and what steps should be taken if they do not, exemplifies the issue. Questions regarding the magnitude of injury risks in sport are issues of fact and can be quantified via the results of injury surveillance studies. Risks are neither high nor low in isolation; they are relatively high or low with reference to other activities or across groups participating in an activity. Issues of the acceptability of a given degree of risk are value dependent. Research regarding perceptions of risk reveals wide variations in the degree of risk people view as acceptable. Factors impacting on risk perception include whether the risks are well known and understood, whether they are 'dread' risks and the degree to which people undertake the risks voluntarily and feel they have control over them. Based on the evidence currently available, the risks to children playing rugby do not appear to be inordinately high compared with those in a range of other childhood sports and activities, but better comparative information is urgently needed. Further evidence, however, should not necessarily be expected to result in the resolution of acceptable risk debates—pre-existing values shape our perspectives on whether new evidence is relevant, valid and reliable.